De Novo Aneurysm Formation After Stereotactic Radiosurgery of a Residual Arteriovenous Malformation: Case Report - Huang, Paul P.; Kamiryo, Toshifumi; Kim Nelson, P. (American Journal of Neuroradiology, 2001)
Summary: We report a case of a 19-year-old woman who underwent radiosurgical treatment of a residual arteriovenous malformation. Nine months after treatment, repeat angiography revealed a de novo paranidal aneurysm that was treated endovascularly. We postulate that changes in flow dynamics or vessel integrity after radiosurgery contributed to the formation of her de novo aneurysm.